The New Semianalytical Technique for the Solution of Fractional-Order Navier-Stokes Equation. (20th April 2021) - Shah, Nehad Ali; Areshi, Mounirah; Chung, Jae Dong; Nonlaopon, Kamsing
Abstract : In this paper, we introduce a modified method which is constructed by mixing the residual power series method and the Elzaki transformation. Precisely, we provide the details of implementing the suggested technique to investigate the fractional-order nonlinear models. Second, we test the efficiency and the validity of the technique on the fractional-order Navier-Stokes models. Then, we apply this new method to analyze the fractional-order nonlinear system of Navier-Stokes models. Finally, we provide 3-D graphical plots to support the impact of the fractional derivative acting on the behavior of the obtained profile solutions to the suggested models.